FAKTOR-FAKTOR SOSIAL BUDAYA DALAM PENINGKATAN DAYA SAING : Kasus Industri Logam Di Sukabumi, Ceper, Tegal dan Pasuruan - Rusydi Syahra (Jurnal Masyarakat dan Budaya, 2004)
This article is aimed at reporting some socio-cultural factors that may have constrained the improvement of the competitive advantage of Indonesian small and medium enterprises (SME). Based on the data collected from metal industries in four locations, namely Sukabumi, Tegal, Ceper and Pasuruan, the study found that the products of these industries, especially automotive parts and components have not been not able to compete in local markets with those from China, not to mention those from Japan and other advanced industrial nations, both in quality and price. Using social capital approach in depicting the existing industriesâ€™ situation the study puts forward some important socialcultural factors that have contributed to the competitive disadvantage. These include: (1) the inability to depart from traditional way producing goods in which the quality of products is largely dependent on the skills of a master or â€œmpuâ€ instead of systematic scientific knowledge as a characteristic in modern industries; (2) a subsistent mentality indicated by the reluctance to develop into a bigger industry which is beyond the controllability of the owner/manager; and (3) the reluctance to form and commit in an industrial association, while this kind of organization may prevent members from cut-throat competition as has prevailed until recently. The study concludes as long as the situation remains, the products of these industries will remain to stay in the lower segment of the market, and more importantly, these industries will have very little chance of becoming business partners and suppliers of parts and components for big assembling industries. This means that in the foreseeable future the local markets will still be flooded by imported metal industrial products, and foreign small and medium metal industries will still hold a dominant position as suppliers for local automotive assembling industries.